2002
DOI: 10.1101/gr.198602
|View full text |Cite
|
Sign up to set email alerts
|

Domain-Level Differences in Microsatellite Distribution and Content Result from Different Relative Rates of Insertion and Deletion Mutations

Abstract: Microsatellites (short tandem polynucleotide repeats) are found throughout eukaryotic genomes at frequencies many orders of magnitude higher than the frequencies predicted to occur by chance. Most of these microsatellites appear to have evolved in a generally neutral manner. In contrast, microsatellites are generally absent from bacterial genomes except in locations where they provide adaptive functional variability, and these appear to have evolved under selection. We demonstrate a mutational bias towards del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 31 publications
4
38
1
2
Order By: Relevance
“…Including all loci showing heterogeneous repeat copy numbers, the overall rate of repeat deletions was significantly higher than that of repeat insertions (60.6 vs 39.4%; p = 0.0276; Supplementary Table 9), in agreement with previous reports [44]. In addition, in two loci (Mpn108b and Mpn111) almost all alleles with >10 repeats showed extensive intrastrain heterogeneity in the repeat copy number in sharp contrast to the high homogeneity in alleles with <10 repeats (Table 2), consistent with the notion that higher copy number alleles are more unstable than lower copy number alleles [45].…”
Section: • Different Levels Of Intrastrain Copy Number Variationsupporting
confidence: 81%
“…Including all loci showing heterogeneous repeat copy numbers, the overall rate of repeat deletions was significantly higher than that of repeat insertions (60.6 vs 39.4%; p = 0.0276; Supplementary Table 9), in agreement with previous reports [44]. In addition, in two loci (Mpn108b and Mpn111) almost all alleles with >10 repeats showed extensive intrastrain heterogeneity in the repeat copy number in sharp contrast to the high homogeneity in alleles with <10 repeats (Table 2), consistent with the notion that higher copy number alleles are more unstable than lower copy number alleles [45].…”
Section: • Different Levels Of Intrastrain Copy Number Variationsupporting
confidence: 81%
“…In CDSs, trinucleotide motifs were predominant (33 %). This result is in accordance with previous studies, which showed that selection against frameshift mutations limits nontriplet SSRs expansion in CDS regions (Metzgar et al, 2002).…”
Section: Discussionsupporting
confidence: 83%
“…Primers will not contain G/C runs of >4 bp (G/C bases will be as evenly spaced as possible), and primers will not contain repetitive sequences (AAAAA, GAGAGA, etc). It is especially important to avoid repetitive sequences because they are far more common in eukaryotic genomes than sequences of greater complexity [38], and will therefore be more likely to misanneal to host sequences.…”
Section: Primer Choicementioning
confidence: 99%